Dispersers efficiency on granulometric analysis of soil materials having argillic horizon - Carvalho, Marco Antônio de; Freire, Jeziel Cardoso; Curi, Nilton; Bahia, Victor Gonçalves (Pesquisa Agropecuaria Brasileira, 2014)
The efficiency of dispersers on granulometric analysis was studied using nine different soil materials having argillic horizon. Sodium hydroxide, sodium hexametaphosphate, and sodium hexametaphosphate + sodium carbonate were utilized as chemical dispersers, using slow and fast shaking, in the presence and absence of abrasive agent. The dispersers efficiency was evaluated through the clay percentage which was determined by pipette and hydrometter methods. The data revealed that the presence of coarse sand as abrasive agent upon desaggregation was efficient, as well as the slow shaking, mainly when associated with the abrasive agent. The pipette method was more efficient than the hidrometter in terms of clay determination. The sodium hydroxide and sodium hexametaphosphate had similar action for these soil materials.